Effect of electromagnetic treatment combined with chlorination on water quality in sea lion recreational pools - Carlos Augusto Morales-Paredes; Francisco Díaz-Regañón; Nuria Boluda-Botella; María Dolores Saquete; Edwin Fernando Morales-Paredes; Raúl Berenguer; Joan Manuel Rodríguez-Díaz (Case Studies in Chemical and Environmental Engineering, 2024)
Water parks often use chlorine for water disinfection despite its ineffectiveness and health risks. This research explored the efficacy of combining electromagnetic treatment (EMT) with chlorination in disinfecting swimming pool water. Water samples, with different organic loads, were subjected to EMT-chlorination tests. EMT significantly affected the physicochemical parameters of the water, notably reducing turbidity by 50 % and decreasing COD levels compared to systems without EMT. The system with EMT reported lower chlorine consumption, suggesting a lower formation of chlorogenic by-products. Therefore, it is evident that the combined method can decrease the levels of organic contamination in the water, reduce the presence of algae, and minimize the consumption of conventional chemical disinfectants, thus reflecting an interesting synergy between EMT and chlorination, which could be advantageous from a health, environmental and economic perspective.